Input of a Multi-Disciplinary Meeting in the Treatment of Osteoarticular Infections in French War Casualties - Grosset, Antoine; Mangin, Philippe; MacNab, Christine; Pfister, Georges; de l'Escalopier, Nicolas; Cournac, Jean-Marie; Aletti, Marc; Samson, Thierry; Rigal, Sylvain; Mathieu, Laurent (Military medicine, 2019)
Extremity war-wounds present an elevated risk of infection and compromise reconstructive procedures. In a French military hospital, a multi-disciplinary meeting (MDM) was created to standardize the care given to soldiers with osteoarticular infection. The aim of this study was to evaluate the usefulness of MDM decisions. An observational case study was performed including the French wounded at war treated for an osteoarticular infection between 2004 and 2016. They were separated into two groups according to their time of management: before (group A) or after (group B) the MDM creation in September 2010. Various operative and bacteriological parameters were analyzed retrospectively. A questionnaire was created to evaluate healthcare professionals' satisfaction toward the usefulness of the MDM on their practice. During the study period, 38 patients were included: 19 in group A and 19 in group B. Initial tests found an infection with one pathogen in 15 patients, an infection with 2 pathogens in 11 patients, and an infection with 3 or more pathogens in 12 patients. Enterobacter cloacae was the most common pathogen. Pseudomonas aeruginosa and Escherichia coli were also frequent. The mean number of samples taken to conduct the bacteriological tests per operating session was significantly higher for group B than for group A. Twelve of the 14 questioned healthcare professionals believed the MDM was very useful in their patient management. The MDM seems to have had a beneficial impact on orthopedic surgeon practices. A significant increase of the number of samples taken was the most obvious sign that the French recommended practices for osteoarticular infections were followed since the creation of MDM.